Theories of market selection: A survey - Luca Fontanelli (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2023)
We provide a survey of the main mechanisms of market selection used in economics. We gather them in three theoretical paradigms (rational equilibrium, Simonesque and evolutionary), that we try to reconcile in terms of underlying laws of selection. We show that the three paradigms have been converging in their focus on firm heterogeneity and increasing returns. These selec- tion mechanisms are however fostered by theories which differ in terms of sources of increasing returns, generating mechanisms of firm heterogeneity, firm rationality and emphasis on equilibrium states vis-a-vis out-of-equilibrium dynamics. Our discussion suggests that the convergence between the three theoretical paradigms is taking place in the direction of research, which is aimed at the replication of empirical patterns related to firm heterogeneity, rather than in the theory underlying selection mechanisms.
Keywords: L10; D20; D40; 330; Selection; competition; monopolistic competition; quasi-replicator; Gibrat's Law